2022
DOI: 10.3389/fonc.2022.966624
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study on the checkout rate of circulating tumor cells and the prediction of efficacy of neoadjuvant therapy and prognosis in patients with HER-2-positive early breast cancer

Abstract: BackgroundNeoadjuvant therapy is a standard treatment for patients with large, nonmetastatic breast cancer and may allow breast-conserving surgery after tumor downsizing while decreasing the risk of subsequent relapse. Dynamic changes of circulation tumor cells (CTCs) have a role in predicting treatment efficacy of breast cancer. However, the relationship between CTC enumeration before neoadjuvant therapy and pathologic complete response rate is still uncertain.MethodsThe study was exploratory. A total of 50 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…With the development of detection techniques, novel methods such as microgels and antifouling nanofilm could facilitate in the separation and purification of CTCs, which could promote the CTCs to enter the clinic ( 66 68 ). Although the utility of CTC detection was not included in the clinical practice guidelines of BC, many studies have shown its great potential in the management of BC patients ( 69 , 70 ). For instance, the results obtained from Chakraborty’s group encouraged the incorporation of CTC quantification as a prognostic marker and for minimally invasive tumor burden assessment in multiple myeloma ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the development of detection techniques, novel methods such as microgels and antifouling nanofilm could facilitate in the separation and purification of CTCs, which could promote the CTCs to enter the clinic ( 66 68 ). Although the utility of CTC detection was not included in the clinical practice guidelines of BC, many studies have shown its great potential in the management of BC patients ( 69 , 70 ). For instance, the results obtained from Chakraborty’s group encouraged the incorporation of CTC quantification as a prognostic marker and for minimally invasive tumor burden assessment in multiple myeloma ( 71 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, our group has developed an innovative epithelial cell adhesion molecule (EpCAM) recognition peptide-functionalized magnetic nanoparticles (Pep@MNPs) that can be used to efficiently capture rare epithelial CTCs in 2.0 ml whole blood from patients with various solid tumors ( Bai et al, 2014 ; Liu et al, 2017 ; Yue et al, 2018 ; Xu et al, 2019 ; Tan et al, 2021 ). Pep@MNPs has superior sensitivity (54%—69%) to CellSearch in breast cancer patients on account of smaller diameter and higher density of recognition peptides on the surface of magnetic nanoparticles ( Bai et al, 2014 ; Liu et al, 2017 ; Zhou et al, 2022 ). Lower producing cost of peptides in Pep@MNPs becomes another more attractive benefit in clinical application as compared to CellSearch .…”
Section: Introductionmentioning
confidence: 99%